2019
DOI: 10.1177/0098628319834198
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Student Success in Statistics Courses by Tapping Diverse Cognitive Abilities

Abstract: Skill in statistical analysis and interpretation are key areas of expertise for psychology majors seeking graduate school admittance and future employment. However, students can be reluctant to engage in their statistics course and may struggle to find success. One possible way to increase engagement and student learning is to teach in a way that taps multiple areas of cognitive ability through organizing instruction according to Robert Sternberg’s theory of triarchic intelligence. This approach to instruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…According to Riwajanti (2019), who hold emphasized as following: -"Funds can be utilized for empowerment activities/programs, useful for the ummah... however, is not easy because the takmir might have different backgrounds, have different understandings…these differences sometimes could also raise conflicts of thinking". (Riwajanti, 2019, p201 Miller (2019) have argued that the GCA is the depict same with intelligence variables that they are empirical evidence supports the importance and predict antecedent of leadership. This is also alternatively referred to as the lead intelligence or qualities in several studies.…”
Section: Masjid Fundingmentioning
confidence: 98%
“…According to Riwajanti (2019), who hold emphasized as following: -"Funds can be utilized for empowerment activities/programs, useful for the ummah... however, is not easy because the takmir might have different backgrounds, have different understandings…these differences sometimes could also raise conflicts of thinking". (Riwajanti, 2019, p201 Miller (2019) have argued that the GCA is the depict same with intelligence variables that they are empirical evidence supports the importance and predict antecedent of leadership. This is also alternatively referred to as the lead intelligence or qualities in several studies.…”
Section: Masjid Fundingmentioning
confidence: 98%
“…As for other dimensions of graduate study success, scientific research has not provided a conclusive answer. For example, the primary empirical studies find no predictive validity of the GRE toward degree completion [19,[28][29][30][31][32][33], with the most recent study pointing in the opposite direction and showing that scores on GRE-V and GRE-AW, but not GRE-Q, have a large effect in predicting persistence to a PhD degree versus dropout [34]. The metaanalyses, which correct for statistical artifacts of primary studies (e.g., the restriction of range of a predictor), also indicate a small but positive significant relationship between the GRE and degree completion [25,26,35].…”
Section: Gre As a Predictor Of Graduate Study Success: Review Of Lite...mentioning
confidence: 99%
“…No relationship: Petersen et al, 2018;Sealy et al, 2019) Positive relationship: the higher the GRE scores, the longer the time Lorden et al, 2011) Negative relationship: the higher the GRE scores, the shorter the time (Frasier, 2013), also depending on the field of study (Miller, 2013) Graduate degree completion Lorden et al, 2011;Lott et al, 2009;Miller et al, 2019;Petersen et al, 2018) One study is an exception: GRE-V was found to be predictive for degree completion of both masters' and doctoral students, and GRE-Q was predictive only for degree completion of masters' students.…”
Section: Time To Graduate Degreementioning
confidence: 99%
“…No relationship : Zimmermann et al, 2018 Graduate Record Examinations Subject (Physics) Faculty ratings Graduate degree completion (Miller et al, 2019) The study of Miller et al (2019) was heavily criticized for several issues in research design and statistical approach (Weissman, 2020), thus suggesting that the finding must be regarded with a lot of caution.…”
Section: Thesis Performancementioning
confidence: 99%
See 1 more Smart Citation